Analisis Kelayakan Ekonomi dan Finansial Pada Proyek Kawasan Pembangunan Perusahaan Siap Bangun (Studi Kasus: Perumahan Griya Sukasari Subang) - Yusup Yulianto; Endang Setiadi Permana; Reza Cahya Nagara (Jurnal Sipil Terapan, 2023)
In the era of globalization, the increasing rate of population growth will affect the need for housing. This need becomes a problem if the continuous increase in demand can cause land prices to increase. It is known that investment in property is very promising and is increasingly in demand by the public both in the short and long term. In this research, the building of housing in Sukasari Village will be very strategic considering that this area is starting to develop an industrial area. To meet residential needs, the developer built 16 housing units on 1900 m2 of land at that location. The feasibility obtained from the 16 unit Housing Development Project was carried out in the form of an analysis to determine investment and financial feasibility based on the Net Present Value, Benefit Cost Ratio, Internal Rate of Return, Return on Investment, Return on Equity, Break Even Point and Payback Period. The profit obtained is with an NPV value of Rp. 1,284,651,362 (NPV > 0), BCR = 1.18 (BCR > 1), BEP in position 9 housing units sold, PP in the 10th month, IRR value = 118%, ROI and ROE have a level and ratio of 52%, moderate conditions make a profit with an NPV value of Rp. 85,000,830 (NPV > 0), BCR = 1.02 (BCR > 1), BEP in the position of 9 units sold, PP for 6 years, IRR value of 102%, ROI and ROE have a ratio of 6%. Meanwhile, in pessimistic conditions suffered a loss with an NPV value of Rp. 1,077,912,437, BCR 0.64 < 1, BEP does not have a break-even point, and the break-even time or PP occurs in the 13th year which can be interpreted as not breaking even, and the IRR value is 99%, ROI and ROE have a ratio level of 0.40%. It was concluded that the 16-unit housing development project could be profitable and feasible to implement, optimistic conditions with the construction process being completed and the housing units being sold in full in the 12th month.